STRATEGI PEMBELAJARAN GURU DALAM MENGEMBANGKAN ASPEK PERKEMBANGAN MORAL DAN AGAMA ANAK USIA DINI PADA KELOMPOK B DI TK NEGERI HINDU WIDYA KUMARA - Ni Wayan , Puspita Dewi; Perbowosari, Heny; Ida Ayu , Adi Armini (Pratama Widya: Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood education is first and foremost education so learning must also be discussed because of the past early development. The importance of early education causes teachers to really choose the best learning strategy. The development of globalization requires people to have good morals in behavior and must have strong trust. Children are the nation’s next-generation so development must be considered. The aspect of moral and religious development becomes very important to consider because good stimulation of moral and religious development will have a positive impact on children’s behavior and belief in God. Are the issues to be discussed, among others (1) What is the learning strategy undertaken by teachers in developing the moral and religious aspects of early childhood in group B at TK Negeri Hindu Widya Kumara? (2) How is the development of the teacher in developing moral and religious aspects of early childhood in group B at TK Negeri Hindu Widya Kumara? (3) What is the development of the teacher in developing moral and religious aspects of early childhood in group B at TK Negeri Hindu Widya Kumara? The theory used is the theory of behaviorism and moral theory. This research uses qualitative research. Data collection methods are observation, interview, document study and literature study. The collected data were analyzed using qualitative descriptive analysis methods with steps of reduction, data presentation, and conclusion. The results showed the importance of choosing appropriate learning strategies for early childhood education teachers to develop aspects of moral and religious development. In addition, it also discusses various strategies in early childhood education institutions to be able to develop aspects of moral and religious development, as well as provide various development and efforts of teachers in developing aspects of children’s moral and religious development